`More Children, More Happiness?': New Evidence from Elderly Parents in China - Yanyan Gao; Zhaopeng Qu (Global Labor Organization (GLO), 2019)
In this paper, we test the conventional wisdom in developing countries of `more children, more happiness' by exploiting the cohort and provincial variations of elderly parents exposed to the one-child policy in China. Using nationally representative survey data from the 2015 China Health and Retirement Longitude Survey, the results from both the ordinary least square and two-stage least square methods find that more children can enhance elderly parents' subjective well-being (SWB) measured with either life satisfaction or depression mood. The effect is channelled by raising their satisfaction with children and receiving in-kind transfers from children. The heterogeneity analysis also shows that the effect of children on parents' life satisfaction is heterogenous to sex composition, first-birth gender, and parents' age. Our study provides new causal evidence of the impact of fertility on elderly parents' SWB from a developing economy.
Keywords: J13; J14; I18; I31; 330; children; happiness; life satisfaction; elderly parents; depression; China